Spectacle compliance among adolescents in Southern India: Perspectives of service providers - Anuradha Narayanan; Shuba Kumar; Krishna Kumar Ramani (Indian Journal of Ophthalmology, 2018)
Purpose: Compliance to spectacle wear is vital to elimination of avoidable blindness among schoolchildren. This study aims to understand the barriers to compliance and strategies to overcome the barriers from the perspectives of the service providers of the school vision-screening model. Methods: A snapshot qualitative study using focus group discussions (FGDs) was conducted among the service providers including eye care professionals (ECPs) and social workers that are part of the school screening program. Sessions were audio recorded and transcribed. Themes were formed following inductive coding using a conceptual framework. Results: Out of the three FGDs, two were with ECPs and one with social workers. Four subthemes identified under the barriers were poor awareness, spectacle-related, psychosocial, and financial barriers. Unique barriers according to the service providers included nonuse of spectacles by asymptomatic children, children with unilateral refractive errors and those with emmetropic parents. Service providers also brought out parent's feelings of guilt, doubts about their children's impaired vision, the negative self-image among children, and difficulties in obtaining funding to support the costs of screening. Solutions that emerged included the personal visit of professionals for spectacle distribution and counseling parents, demonstration of improvement in vision for activities that were difficult for the children without spectacles and rewarding, and role modeling of compliant children. Conclusion: This study had identified unique barriers and solutions from the perspectives of the service providers. The suggested strategies would aid in an effective schoolchildren vision screening practice to enhance compliance to spectacle wear.